Determinants Of Labor Absorption In The Creative Economy Sector: A Case Study Of 34 Provinces In Indonesia - Muhammad Hafidz; Neli Aida (International Journal of Economics, Business and Innovation Research, 2025)
Labor absorption is an important indicator in measuring the success of economic development, especially in fast-growing sectors such as the creative economy. This study aims to analyze the influence of the average wages of creative economy workers, education level, and internet use on labor absorption in the creative economy sector in 34 provinces in Indonesia during the period 2018 to 2021. In addition, this study also examines whether there are significant differences in the absorption of creative economy labor before and during the Covid-19 pandemic. The results of the study show that the average wage variable of creative economy workers has a negative and insignificant influence on labor absorption. Meanwhile, the level of education and internet use have a significant positive influence on the absorption of labor in the creative economy sector. In addition, there is a significant difference in the number of creative economy workers between before and during the Covid-19 pandemic, where during the Covid-19 pandemic the number of Creative Economy Workers decreased compared to before the occurrence of Covid-19.